IMPLEMENTATION INFORMATION TECHNOLOGY GOVERNANCE IN LICENSING SERVICE AT SUMEDANG REGENCY - M. Irwan Tahir; Mesy Faridah Hendiyani; Dedeh Maryani; Dwi Indah Kartika (Sosiohumaniora, 2022)
This study aims to describe the implementation of information technology governance at the One Stop Integrated Service (PTSP) in Sumedang Regency. This study uses a descriptive method, with the IT Governance theory from Weill and Ross (2004) as theoretical lens with dimensions consisting of IT Principles, IT architecture, IT infrastructure, business application requirements, and Information Technology Investment and Priority Determination proposed by as an analytical tool. Data were collected through observation, interview, and secondary sources. Research informants were determined by purposive sampling according to the research objectives with informants consisting of stakeholders in the implementation of Electronic-Based Government Systems (SPBE) in Sumedang Regency. The results of the study indicate that the overall dimensions of IT Governance have improvements that supports the achievement of the objectives of the SPBE implementation as national program.